Interactions Between Migration, Forest Crime, and Land Use Change in Tekirdağ, Türkiye - Ünal, Hasan Emre; Günlü, Alkan; Sivrikaya, Fatih; Bulut, Sinan (Kastamonu University, 2025)
Aim of study: This study aims to investigate the interactions between land use classes, population change, and forest crimes in the Tekirdağ Forest Planning Unit for the period 2007-2023. Area of study: Tekirdağ was chosen as the case study area because it is one of the provinces that receive the most immigration in Türkiye. Material and method: Stand maps, population information, and forest crime numbers were obtained for use in the study. Land use classes for 2008 and 2016 were created using stand maps. Additionally, forest crime numbers for the 2002-2023 period and population data for the 2007-2023 period were provided. Changes in land use classes, population, and forest crimes were examined according to the relevant years, and the relationships between them were investigated. The relationships between population and forest crimes were determined by Pearson's correlation coefficient. Main results: The most significant changes in land use classes were determined as an increase of 6138.8 ha in broadleaf forests and a decrease of 13673.0 ha in agricultural areas. During the 2007-2023 period, the population increased continuously at variable rates. The relationships between annual population and forest crimes were examined in the 2007-2023 period, and it was determined that the highest relationship was negative between population and grazing crime (r=-0.641). Research highlights: In-migration in the study area and the decrease in the rural population have been effective in forest crimes committed in the region. In-migration has led to a decrease in grazing crime and an increase in individual occupation crimes in rural areas.